Simultaneous occurrence of bilateral retroperitoneal neuroblastoma and bifocal malignant mixed germ cell tumor in a pediatric patient with 16p11.2 microdeletion syndrome: a case report - Fan, Qian-Xiu; Zhuang, Xia-Mei; Wen, Rong; Wu, Xing-Han; Luo, Hai-Yan; Yang, Hai-Xia; Kuang, Wen-Yong; Zhang, Ben-Shan; Zheng, Min-Cui; Wu, Pan (Frontiers in Endocrinology, 2026)
Central nervous system germ cell tumors are rare intracranial neoplasms that predominantly occur in pediatric populations and exhibit characteristics similar to those of gonadal and extragonadal germ cell tumors. Neuroblastoma (NB) represents the most common type of extracranial solid tumor in children, typically arising in tissues with sympathetic innervation. We present a case involving a 14-year-old male patient diagnosed with bilateral intracranial mixed germ cell tumors and concurrent bilateral retroperitoneal ganglioneuroblastoma. To the best of our knowledge, this is the first documented instance of the co-occurrence of these two distinct neoplastic entities. Additionally, Whole-exome sequencing (WES) of the blood sample identified a chromosomal deletion consistent with the 16p11.2 microdeletion syndrome. Furthermore, a heterozygous missense variant in the ALK gene (p. Arg1275Gln) was identified.